2016
DOI: 10.1055/s-0036-1592151
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus Nonsurgical Treatments of Acute Primary Patellar Dislocation with Special Emphasis on the MPFL Injury Patterns

Abstract: The objective of the present study was to compare the clinical results of the surgical versus nonsurgical treatments of acute primary patellar dislocations with a medial patellofemoral ligament (MPFL) injury in the nonoverlap region with the vastus medialis oblique. In this study, 62 patients with an acute patellar dislocation and a concurrent MPFL injury in the nonoverlap region were randomly divided into two groups based on their birth years (even vs. odd years) and received either surgical or nonsurgical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 25 publications
4
35
0
1
Order By: Relevance
“…This is consistent with the study conducted by Ji et al ,36 who performed an open repair of the MPFL based on their description to the MPFL injury pattern. They found that the femoral insertion of the MPFL is the main injury location in primary patellar dislocations and requires a ‘single-point fixation’ repair.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the study conducted by Ji et al ,36 who performed an open repair of the MPFL based on their description to the MPFL injury pattern. They found that the femoral insertion of the MPFL is the main injury location in primary patellar dislocations and requires a ‘single-point fixation’ repair.…”
Section: Discussionsupporting
confidence: 92%
“…After that, we compared the clinical results of the surgical versus nonsurgical treatments of acute primary patellar dislocations with a MPFL injury in the nonoverlap region with the VMO, and we concluded that the surgical treatment of the MPFL injuries in the nonoverlap region achieved better clinical outcomes and improved subjective knee function compared with the conservative therapy. 31 We confirmed our hypothesis that the MPFL with or without the VMO overlap is critical to the success of the treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Four studies randomized both groups to nonoperative interventions. 2 , 39 , 45 , 49 Significant methodological weaknesses existed in the literature; information specifying the randomization protocol was lacking (eg, failing to specify who performed the random allocation sequence and enrolled/assigned participants) in up to 9 studies, ¶ 4 studies provided insufficient information regarding the interventions to permit replication, 2 , 7 , 35 , 46 4 did not specify the location of the population recruited, 7 , 24 , 38 , 46 3 studies provided no evidence for how the sample size was estimated (ie, showed no power calculations), 24 , 34 , 35 and 1 did not outline the follow-up period. 7 Only 3 studies satisfactorily reported CIs, making an assessment of the effect size difficult.…”
Section: Resultsmentioning
confidence: 99%